Perlindungan Konsumen Bagi Pembeli Dalam Transaksi Di Platform E-Commerce - Hamamah, Fatin; Soekarno, Dimas Pratama (FOCUS: Jurnal of Law, 2021)
The ease of access to the Internet has increased the number of e-commerce consumers for reasons including practicality, easy-to-use payment systems, time efficiency, and the many preferential prices of online businesses. This is for many reasons. However, considering the number of online companies, behind all the conveniences and benefits provided, there is another concern that online companies are responsible for e-commerce consumers. In the context of the current Indonesian consumer protection law (namely Law Number 8 of 1999 concerning Consumer Protection), the rights and obligations of consumers and business actors have been clearly and firmly regulated. The rights and obligations of consumers are regulated in Articles 4 and 5 of Law Number 8 of 1999, while the rights and obligations of commercial actors are regulated in Articles 6 and 7 of Law Number 8 of 1999.